Electromyographic validation of the trapezius and serratus anterior muscles in rowing exercises with closed grip - Büll, Marilena Longo [UNESP]; Freitas, V. [UNESP]; Vitti, M. [UNESP]; Rosa, G. J M [UNESP] (My University, 2002)
Because the lack of specialized textbooks, the select of basic exercises for physical conditioning programmes is based on empirical knowledge. This fact led the authors to propose the study on electromyographic activity of the trapezius (upper portion) (TS) and the serratus anterior (lower portion) (SI) muscles in rowing exercises with closed grip in three different modalities. The tests were carried out with 24 male volunteers, 18 to 25 years old, by using a two-channel TECA TE 4 electromyograph and Hewlett Packard surface electrodes. For exercises execution, a long bar made of light wood was used. TS acted significantly in the three different modalities, that is, upright, sitting and bent over, while SI acted preferentially in upright and sitting rowing exercises, justifying their inclusion as basic exercises in physical conditioning programmes.
Keywords: adult; calibration; controlled study; electrode; electromyography; exercise; hand grip; human; human experiment; information; kinesiology; male; muscle action potential; muscle contraction; normal human; shoulder girdle; sitting; sports medicine; standing; training; trapezius muscle; validation process; Adolescent; Adult; Arm; Electromyography; Exercise; Hand Strength; Humans; Male; Muscle, Skeletal; Physical Fitness; Reference Values; Reproducibility of Results; Shoulder